Kinematic gait analyses in healthy Golden Retrievers - Silva,Gabriela C.A. (2014)
Kinematic analysis relates to the relative movement between rigid bodies and finds application in gait analysis and other body movements, interpretation of their data when there is change, determines the choice of treatment to be instituted. The objective of this study was to standardize the march of Dog Golden Retriever Healthy to assist in the diagnosis and treatment of musculoskeletal disorders. We used a kinematic analysis system to analyse the gait of seven dogs Golden Retriever, female, aged between 2 and 4 years, weighing 21.5 to 28 kg, clinically normal. Flexion and extension were described for shoulder, elbow, carpal, hip, femorotibialis and tarsal joints. The gait was characterized lateral and had accepted hypothesis of normality for all variables, except for the stance of hip and elbow, considering a confidence level of 95%, significance level α = 0.05. Variations have been attributed to displacement of the stripes during movement and the duplicated number of reviews. The kinematic analysis proved to be a consistent method of evaluation of the movement during canine gait and the data can be used in the diagnosis and evaluation of canine gait in comparison to other studies and treatment of dogs with musculoskeletal disorders.